Synthesis and physical-chemical properties of 3-benzyl-8-propylxanthinyl-7-acetic acid and its derivatives - E. K. Mikhalchenko; K. V. Аleksandrova; S. V. Levich; D. M. Sinchenko (Zaporozhye State Medical University, 2017)
Introduction. Heterocyclic compounds play an important role in the metabolic processes of human organism. Structures of vitamins, nucleotides, chromoproteins are based on Nitrogen-containing heterocycles (purine, pyrimidine, thiazole etc). Thus, it was obvious to use these organic substances as basic molecules for synthetic research of biologically active compounds which could be used for treatment of different pathological processes. In their research, some scientist pay special attention to xanthine derivatives that are well-known low toxic natural compounds with wide spectrum of pronounced pharmacological properties (antioxidant, diuretic, antibacterial, anti-inflammatory etc). Insertion of carboxyl group in the structure of xanthine molecule is a prospective ability of its synthetic potential increasing. Aim of our research was the development of method of 3-benzyl-8-propylxanthinyl-7-acetic acid and its derivatives synthesis and studying their physical-chemical properties. Materials and methods. Melting points were determined using capillary method on DMP (M). 1Н NMR-spectra were recorded by Varian Mercury VX-200 device (company «Varian», USA) solvent - (DMSO-d6), internal standard - ТМS. Elemental analysis of obtained compounds was produced on device Elementar Vario L cube. Results and discussion. We selected 3-benzyl-8-propyl xanthine as initial compound for our study. By its interaction with chloroacetic acid, chloroacetamide or propyl chloroacetate in DMF in the presence of calculated amount of NaHCO3 we synthesized 3-benzyl-8-propylxanthinyl-7-acetic acid its ester and amide. At the same time we found that obtaining of xanthinyl-7-acetic acid by hydrolysis of its ester produced with higher yield. On the next stage of our research we synthesized a number of water-soluble salts of 3-benzyl-8-propylxanthinyl-7-acetic acid by reaction of acid with different primary and secondary amines. The structures of all obtained compounds were proved by the elemental analysis and 1H NMR-spectroscopy. Conclusions. Obtained results of our work can be used for further search of biologically active compounds among xanthine derivatives with carboxyl residue.